Uma perspectiva crítico-racial da História da música brasileira (1926) de Renato Almeida - Jonatha Maximiniano do Carmo (2022)
This doctoral thesis aims at identifying and critically describing the racist discourse found in the História da música brasileira (History of the Brazilian music) written by Renato Almeida in 1926, by examining how the discourse of racial whitening, prevailing at that time, was transposed to the concept of Brazilian music. The research also aims at identifying and interrelating the ideas of race and mestiçagem (miscegenation) to the writings of important figures pertaining his ‘intellectual sociability network’: Afrânio Peixoto, Graça Aranha and Ronald de Carvalho who, just like Renato Almeida, were white, men and graduated in Law and Medical Schools, and who also held important positions within the Government. In order to achieve these purposes, the research focused on the first two decades of the 20th Century, especially around the 1922 Semana de Arte Moderna (Modern Art Week). Based on bibliographic and electronic research, the fundamental concepts were defined so as to delimit the theme: ‘racism’, present in the works of Silvio de Almeida, Rita Segato, Clóvis Moura and Alberto Guerreiro Ramos; ‘whiteness’, as discussed by authors such as Maria Aparecida Bento, Philip Ewell, Lia Schucman and Richard Miskolci; the concepts of biopower and biopolitics, developed by Michel Foucault e Miskolci and, finally, that of ‘intellectual sociability network’, developed by François Sirinelli and Ângela de Castro Gomes. The study concludes that the concept of mestiçagem (miscegenation) was blended to the ideal of Brazilian classical – or concert – music. It reveals that, within the thought of the racial triangle, indigenous people and Black people appeared as ‘influencers’ or ‘contributors’ to the white civilizational universe. The thesis demonstrates that there is racial discourse in História da música brasileira (1926) by Renato Almeida, which is ideologically determinist and racist, and hides an ideal of cultural, social and thus musical whitenning. It can also be concluded that the exaltation of the mestizo as a symbol of Brazilianness was in fact a masked praise: by considering the mestizo a less indigenous or a less Black person, this meant he or she was becoming more civilized and thus whiter.